The quality of crude glycerine influences the fermentation and nutritive value of Piata grass silage - Schwingel, Alice Watte [UNESP]; Fernandes, Tatiane; Previdelli Orrico Junior, Marco Antonio; Amorim Orrico, Ana Carolina; Lucas, Jorge de [UNESP]; Reis, Ricardo Andrade [UNESP]; Souza, Ronaldo Omizolo de (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2020)
We aimed to evaluate the effects of crude glycerine purity and levels of glycerol on the fermentative profile, microorganisms counting, and nutritional value of Piata grass silage. The experiment was carried out in a 3x3+1 completely randomized factorial design using three different types of crude glycerine [low purity (40% of glycerol), medium purity (60% glycerol), and high purity (80% glycerol)], three doses of glycerol (20, 40, and 60 g/kg DM), and a control (no crude glycerine added) as an additional treatment, which were stored for 80 days. Statistical differences were not observed on fermentative losses of the treatments tested. The increase of glycerol doses resulted in higher levels of non-fibrous carbohydrates and lower levels of fibre components. The addition of low-purity crude glycerine increased the levels of fat and in vitro digestibility of silages. The highest levels of lactic acid and acetic acid occurred in the treatments with 60 g/kg of glycerol when using crude glycerine with a low purity. The lowest lactic acid content was observed in the control treatment and in the lowest dose of glycerol. The highest glycerol dose (60 g/kg), associated with the lowest degree of crude glycerine purity (40%) resulted in the greatest nutritional value and provided the best silage conservation.
Keywords: byproduct of biodiesel; fermentation profile; forage conservation; ruminant feed